Determination of fluoride content in toothpaste using spectrophotometry - Susanti Pudji Hastuti; Devinta Lestari; Yohanes Martono (Universitas Airlangga, 2013)
Background: Intake excessive fluoride in children's teeth are generally marked with white and brown patches. Excessive fluoride of more than 4.0 mg/L can cause a person suffering from poisoning, fragility of the bones (osteoporosis), liver and kidney damage. Knowledge about the spectrophotometry for determination method of fluoride content in commercially available toothpaste is very few. Purpose: The purposes of study were to examine the suitable method for fluoride extraction and to determine out the accuracy, precision, linearity, and stability of the measurement method of fluoride content in toothpaste. Methods: The suitable F extraction method was determined by the comparison among 3 methods of extraction; e.g. the dried samples were immersed in (1) distilled water, (2) 96% HCl, and (3) 96% HNO3; and the validation methods of measurement were the maximum wavelength, standart curve, accuracy test, precision test, and stability test. Results: Result showed that the fluoride extraction by using the concentrated HNO3 was found to have the highest levels of fluoride, followed by hydrochloric acid dissolution (HCl) and distilled water, while the method of validation showed that SPADNS revealed the acceptable accuracy. Precision has the RSD ≤ 2.00%. Furthermore the stability test result showed that the measurement of fluoride less than 2 hours was still reliable. Conclusion: The study suggested that the best result of fluoride extraction from toothpaste could be gained by using concentrate HNO3, and the spectrophotometer (UV-Vis Mini Shimadzu U-1240) and SPADNS have the acceptable accuracy. <span style="font-family: Tribune-Bold; font-size: